DEVELOPMENT OF E-WORKSHEETS BASED ON INQUIRY USING SPECTROPHOTOMETER PRACTICUM TOOLS TO TRAIN SCIENCE PROCESS SKILLS IN LIGHT WAVES MATERIALS - Safitri, Nadiyah; Herlina, Kartini; Permadi, Dimas (INSECTA: Integrative Science Education and Teaching Activity Journal, 2025)
This study aims to develop an inquiry-based e-Worksheet (Electronic Student Worksheets) that is valid, practical, and effective in enhancing science process skills in the topic of light waves with the assistance of Liveworksheet. The research development design used is Design Development Research (DDR), which consists of four stages: analysis, design, development, and evaluation. The results of the product validity test obtained an average percentage score of 90.12%, categorized as very valid. The results of the small-scale test, in terms of readability, achieved an average percentage of 85.2%. In the large-scale test, the practicality test, specifically the student response test, received a score of 82.75%, while the teacher perception test obtained a score of 90%. All average scores from both the small-scale and large-scale tests fall into the very practical category. Secondly, the effectiveness test results from the Paired Sample T-Test showed an average of 0.000, indicating that science process skills were well-trained and showed a significant improvement, with an N-Gain score of 0.63 after the implementation of the inquiry-based e- Worksheet. This means that the inquiry-based e- Worksheet, utilizing spectrophotometer lab equipment to train science process skills in light wave topics, is effectively used in the learning process with a moderate category.